Removal of Malachite Green Dye From Aqueous Media using Helianthus Annuus Seeds Shells as Eco-Friendly Adsorbent: Optimization, Equilibrium, and Kinetic Studies - Hichem Fiala; Hacene Bendjeffal; Hamrouni Achraf; Lahmar Amina; Berredjem Yamina; Hattab Zhour; Gheid Abdelhak (Annals of R.S.C.B., 2021)
The fat diffusion of organic dyes in our environment has become a very serious ecological problem, which needs the improvement of new and low-cost methods for their elimination from aquatic media. In this In this approach, we studied the use of the Helianthus annuus seeds shells as natural, low-cost and eco-friendly adsorbent for the removal of the malachite green (MG) from aqueous media. The Helianthus Annuus seeds shells (HA-Ss) were characterized using various techniques such as FTIR, SEM, and ATG. The sorption tests were performed according to the Batch system, under the effects of four physicochemical factors, including the adsorbent mass (0.0025 and 5 g.L-1), medium pH (1-10), MG initial concentration (10-50 mg/L), and temperature (25-45°C). The removal optimal condutions were found to be 2.5 g/L of Helianthus annuus seeds shells, 20 mg/L as MG initial concentration, and pH 7 for 60 minutes of contact time with a removal efficiency up to 99%. Several kinetic models including pseudo-first order and pseudo-second order were used to describe MG adsorption mechanism, the modeling studies indicated that adsorption mechanism follows the pseudo-second-order kinetic model, and the adsorption isotherms follow the Freundlich model with Qe reached 7.69 mg/g.